Metabarcoding of environmental samples suggest wide distribution of eelgrass (Zostera marina) pathogens in the north Pacific - Damian M. Menning (Pensoft Publishers, 2021)
Seagrass meadows provide important ecological services to the marine environment but are declining worldwide. Although eelgrass meadows in the north Pacific are thought to be relatively healthy, few studies have assessed the presence of known disease pathogens in these meadows. In a pilot study to test the efficacy of the methods and to provide foundational disease biodiversity data in the north Pacific, we leveraged metabarcoding of environmental DNA extracted from water, sediment, and eelgrass tissue samples collected from five widely distributed eelgrass meadows in Alaska and one in Japan and uncovered wide prevalence of two classes of pathogenic organisms – Labyrinthula zosterae and other associated strains of Labyrinthula, and the Phytophthora/Halophytophthora blight species complex – known to have caused decline in eelgrass (Zostera marina) elsewhere in the species’ global distribution. Although the distribution of these disease organisms is not well understood in the north Pacific, we uncovered the presence of at least one eelgrass pathogen at every locality sampled.